Escola Parque: notas sobre a proposta de Anísio Teixeira para o ensino básico no Brasil - Carbello, Sandra Regina Cassol [UNESP]; Ribeiro, Ricardo [UNESP] (My University, 2014)
This article deals with the Park School, a proposal prepared by AnísioTeixeira to organize basic education in Brazil. This is a bibliographic study, anchored in texts produced by the author himself and researchers who are dedicated to their legacy. Records show that the proposed Park School was an experiment, bold and innovative, to arrange a policy for primary education in Brazil. Was expertly planned and stood out in the architectural and pedagogical aspects. Park School has shown that it is possible to provide a quality public education; political commitment and solid educational training are therefore fundamental.

Este artigo versa sobre a Escola Parque, proposta elaborada por Anísio Teixeira para organizar o ensino básico no Brasil. Trata-se de um estudo bibliográfico, ancorado em textos produzidos pelo próprio autor e por pesquisadores que se dedicaram ao seu legado. Os registros mostram que a proposta da Escola Parque era um ensaio, audacioso e inovador, para organizar uma política para o ensino primário no Brasil. Foi eximiamente planejada e destacava-se nos aspectos arquitetônico e pedagógico. A experiência da Escola Parque mostrou que é possível ofertar uma educação pública de qualidade e, para tanto, é fundamental compromisso político e sólida formação docente.
School Park: notes on Anísio Teixeira propositions for basic education in Brazil
Keywords: Public school; Educational Center Carneiro Ribeiro; Educational policy; Escola pública; Centro Educacional Carneiro Ribeiro; Política educacional